Protective effect of a reverse membrane bioreactor against toluene and naphthalene in anaerobic digestion. (22nd July 2021) - Chandolias, Konstantinos; Sugianto, Laurenz Alan Ricardo; Izazi, Nurina; Millati, Ria; Wikandari, Rachma; Ylitervo, Päivi; Niklasson, Claes; Taherzadeh, Mohammad J.
Abstract: Raw syngas contains tar contaminants including toluene and naphthalene, which inhibit its conversion to methane. Cell encasement in a hydrophilic reverse membrane bioreactor (RMBR) could protect the cells from hydrophobic contaminants. This study aimed to investigate the inhibition of toluene and naphthalene and the effect of using RMBR. In this work, toluene and naphthalene were added at concentrations of 0.5–1.0 and 0.1–0.2 g/L in batch operation. In continuous operation, concentration of 0–6.44 g/L for toluene and 0–1.28 g/L for naphthalene were studied. The results showed that no inhibition was observed in batch operation for toluene and naphthalene at concentrations up to 1 and 0.2 g/L, respectively. In continuous operation of free cell bioreactors (FCBRs), inhibition of toluene and naphthalene started at 2.05 and 0.63 g/L, respectively. When they were present simultaneously, inhibition of toluene and naphthalene occurred at concentrations of 3.14 and 0.63 g/L, respectively. In continuous RMBRs, no inhibition for toluene and less inhibition for naphthalene were observed, resulting in higher methane production from RMBR than that of FCBR. These results indicated that RMBR system gave a better protection effect against inhibitors compared with FCBR.